Cystic Adventitial Disease of the Popliteal Vein: A Case Report. (February 2023) - Jing, Zongxu; Zhang, Changming; LI, Xiangtao; Zhang, Huan; Niu, Luyuan; Feng, Yaping; Liu, Yong; Yue, Yunlong; Du, Xuemei; Luo, Xiaoyun
Venous cystic adventitial disease (VCAD) is a rare vascular anomaly located in the common femoral vein in most cases. We describe the case of a 59-year-old female patient with right leg edema who was misdiagnosed with deep vein thrombosis of the lower extremity at another hospital. Magnetic resonance angiography revealed a round mass in the popliteal vein, with a narrow lumen. Considering the location of the lesion, absence of a history of deep venous thrombosis and trauma, and clinical manifestations, the diagnosis is likely a popliteal vein adventitial cyst. Segmental popliteal vein resection and reconstruction were performed using a cylindrical great saphenous vein graft. No joint connection was found during the operation, and the postoperative pathology confirmed VCAD.